Creating value with equity management at Ag Valley Cooperative - Nielsen, Kevin (Kansas State University, 2015)
The main objective of this thesis is to aid Ag Valley Cooperative’s board of directors in the construction of a superior income distribution and equity redemption strategy. The key information provided is a detailed financial analysis and pro forma financial projections. Ultimately, this study focuses on increasing patron value by returning retained patronage refunds in an equitable and timely manner. This paper examines the benefits of eliminating Ag Valley Cooperative’s current equity redemption program, age of patron, and replacing it with a revolving fund. Chapter 1 introduces Ag Valley Cooperative and gives a brief description of the cooperative’s business model. The chapter concludes with the study’s methodology. Chapter 2 briefly examines cooperatives and people who use them. This chapter introduces Cooperative Performance Profile, the financial analysis used in the study. The chapter concludes with a look at cooperative finance theory and equity management. Chapter 3 describes key points of the Cooperative Performance Profile and separates it into five groupings: profitability, liquidity, solvency, efficiency, and size. Analyses are conducted in each category on Ag Valley Cooperative’s historic trends and comparisons to other Nebraska cooperatives. In Chapter 4 Ag Valley Cooperative’s current equity redemption strategy is defined along with four pro forma analyses. The first strategy, S0, assumes the cooperative continues business as normal with estate and age of patron redemption methods. Strategies S1 and S2 interject balance sheet management constraints and revolving fund redemption into the projection. In S1, revolving fund equity redemption is added to distribute any excess equity redemption budget, in S2 the revolving fund method is phased in. Strategy S3 builds upon S2 with a look at the effects and tax consequences of distributing non-qualified equity or retained patronage refunds instead of qualified retained patronage refunds.
Keywords: Cooperative; Equity; Management; Finance; Income; Distribution; Business (0310); Economics, Agricultural (0503); Economics, Finance (0508); Management (0454)